Electronic and spin states of SrRuO 3 thin films: an x-ray magnetic circular dichroism study - Agrestini, Stefano; Hu, Zhimin; Haverkort, Maurits W. (Physical review. B, Condensed matter and materials physics, 2015)
We report a study of the local magnetism in thin films of SrRuO3 grown on (111) and (001) oriented SrTiO3 substrates using x-ray magnetic circular dichroism spectroscopy (XMCD) at the Ru-L2,3 edges. The application of the sum rules to the XMCD data gives an almost quenched orbital moment and a spin moment close to the value expected for the low spin state S=1. Full-multiplet cluster calculations indicate that the low spin state is quite stable and suggest that the occurrence of a transition to the high spin state S=2 in strained thin films of SrRuO3 is unlikely as it would be too expensive in energy.